Augmentation mammoplasty: how it is done, recovery and frequent questions. - Valls , Emilio (Brazilian Journal of Implantology and Health Sciences, 2021)
Cosmetic surgery to insert silicone prosthesis may be indicated when the woman has very small breasts, is afraid of not being able to breastfeed, has noticed a reduction in their size or has lost a lot of weight. But it can also be indicated when a woman has breasts with different sizes or needed to remove the breast or part of the breast due to cancer. This surgery can be done from the age of 15 with parental permission, and is performed under general anesthesia, taking about 45 minutes, and can be with a short hospital stay of 1 or 2 days, or even in an outpatient setting, when he is discharged on the same day.